A simulation study to enhance the gas production rate by nitrogen replacement in the underground gas storage performance - Afshin Davarpanah; Mehdi Mazarei; Behnam Mirshekari (Energy Reports, 2019)
Underground gas storage (henceforth; UGS) is considered as a common method which resolves the seasonality problem of transportation and distribution of gas phase in the oil and gas industries. The main objective of this study is to simulate one of Iranian's depleted gas condensate reservoir and compare different injectivity scenarios especially nitrogen injection to enhance the gas production. Based on the anticipated target rate performance of UGS with a different scenario that was analyzed the effect of injection gas, finding optimum original reservoir pressure, an optimum number of wells. Moreover, abandonment pressure is one of the main concerns for UGS process in partially depleted reservoirs especially in the depleted reservoir to decrease the ultimate recovery. It contains insufficient base gas reserves, and if it may not meet the target withdrawal rate, the original reservoir pressure has been estimated at 250 bar. Consequently, it found that this problem can be addressed by injecting a higher volume of gas in the first cycle and due to the existence of new wells, the maximum injection rate was obtained about 6.1*1010m3.
Keywords: 330; Depleted gas condensate reservoir; Gas production; Gas reserves; Nitrogen injection; Original reservoir pressure; Underground gas storage